Efeito antimelanósico da acerola e metabissulfito de associado à embalagem em atmosfera modificada sobre a qualidade do camarão branco (Litopenaeusvannamei) - Oliveira, Adriene Rosceli Menezes de (2013)
Melanosis in crustaceans consists on the formation of black spots, gathered mainly in the cephalothorax. While not harmful to consumers health, this condition affects the sensory characteristics of food, reducing shelf life and product quality, and originating financial losses. To avoid such loss, one of the most common practices amongst fishermen and farmers is to use sodium metabisulphite (SMS) or other sulfites to prevent melanosis from happening. However, use of these substances should be cautious, for they are often related to respiratory problems in humans. So, organic alternatives, such as extracts from plant, seeds, herbs and fungi have been investigated as substitutes to sulphites in preventing melanosis. Acerola fruit is rich in vitamin C and phenolic compounds, and has antioxidant potential above average among tropical fruits, which makes it a potential antimelanosic agent. This study was aimed at investigating acerola spotential on inhibiting the formation of melanosis and preserving the quality of white shrimp (L. vannamei) longer when compared to SMS, and observe the combined effect of antimelanosic treatments with Modified Atmosphere Packaging, as well. For suchpurpose, samples of shrimp underwent immersion baths in solutions of acerola and SMS for 10 minutes and werethen packed in air,MAP 1 (7N2:3CO2:1O2),MAP 2 (3N2:7CO2:1O2) and vacuum. Every three days, during 21 days, microbiological (total mesophilic and psychrotrophic count, coagulase-positive staphylococci, and Salmonella spp.), physico-chemical (TVB-N, TMA and pH) and sensory (QIM) analyses were performed. Of all sample groups packaged in atmospheric air, the one treated with SMS had shelf-life of 10.5 days, while those treated with acerola solution and the control were acceptable up until 12.3 and 14.6 days, respectively. Samples immersed in acerolasolution, and then packed in MAP 1, MAP 2 or vacuum had shelf lives of 11.6, 11.8, and 14.0 days, respectively, the samples treated with SMS became unacceptable after 16.7, 15.4, and 20.6 days of storage, simultaneously. In most analyses, however, no significant difference was found between treatments, indicating that immersion in acerola solution for 10 minutes inhibitsmelanosisas efficiently as SMS, yet future studies are needed to precisely define the antimelanosiceffect of acerola